Communication in the Implementation of the Community-Based Drinking Water and Sanitation Provision Program (PAMSIMAS) Tanjekwagir Village, Krembung District, Sidoarjo Regency - Novianigsih, Erisa Permadani Bella; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2019)
The Community-Based Drinking Water and Sanitation Provision Program (PAMSIMAS) is a program of the Central Government and Local Governments with support from the World Bank, with the aim of increasing the supply of drinking water and sanitation and improving healthy living behavior among the community. In the implementation of the PAMSIMAS program in Tanjekwagir Village, there are several obstacles including the lack of supporting facilities, especially pipe connections and lack of budget funds. This study aims to analyze and describe the implementation of the PAMSIMAS program and the obstacles in implementing the PAMSIMAS program in Tanjekwagir Village. This type of qualitative descriptive research with the technique of determining the informant using purposive sampling. Research informants were the Head of Tanjekwagir Village, Head of BUMDes, Head of BPSPAM, and community users of the PAMSIMAS program. The research location is in Tanjekwagir Village, Krembung District, Sidoarjo Regency. The data collection techniques are observation, interviews, and documentation. Data analysis techniques from Miles da Huberman (2011: 247) are data collection, data reduction, data presentation, and drawing conclusions. The results of the research on the implementation of the PAMSIMAS program in Tanjekwagir Village are reviewed using communication indicators that have several dimensions. First, tansimisi in the implementation of the PAMSIMAS program uses socialization media directly to the community and utilizes technology by creating a website so that it is easier for people to get information about the PAMSIMAS program in Tanjekwagir Village. Second, clarity in the implementation of the PAMSIMAS program is the target of this program, the PAMSIMAS program was created to provide access to clean water to the community so that people's clean and healthy living behavior can be improved for the better. Third, consistency in the implementation of the PAMSIMAS program is carried out by the Drinking Water Supply Facility Management Agency (BPSPAM) in accordance with PP No. 16 of 2005